2006
DOI: 10.1523/jneurosci.1913-06.2006
|View full text |Cite
|
Sign up to set email alerts
|

Important Contribution of α-Neurexins to Ca2+-Triggered Exocytosis of Secretory Granules

Abstract: ␣-Neurexins constitute a family of neuronal cell surface molecules that are essential for efficient neurotransmission, because mice lacking two or all three ␣-neurexin genes show a severe reduction of synaptic release. Although analyses of ␣-neurexin knock-outs and transgenic rescue animals suggested an involvement of voltage-dependent Ca 2ϩ channels, it remained unclear whether ␣-neurexins have a general role in Ca 2ϩ -dependent exocytosis and how they may affect Ca 2ϩ channels. Here we show by membrane capac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
55
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(58 citation statements)
references
References 98 publications
(141 reference statements)
3
55
0
Order By: Relevance
“…It is important to note, however, that our results do not imply that GABA A R or GABA B R at inhibitory synapses are an exclusive target of Nxph1/α−Nrxn. In fact, we reported previously that the GABA B R-mediated modulation of Ca V 2.2 channels, required for its effect on vesicle release (58), was also impaired at excitatory brainstem synapses of α-Nrxn KO mice (45). Even more importantly, α-Nrxn is abundantly expressed in glutamatergic neurons as well (12) and has unequivocal effects on release from excitatory synapses (9,44,46,78).…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…It is important to note, however, that our results do not imply that GABA A R or GABA B R at inhibitory synapses are an exclusive target of Nxph1/α−Nrxn. In fact, we reported previously that the GABA B R-mediated modulation of Ca V 2.2 channels, required for its effect on vesicle release (58), was also impaired at excitatory brainstem synapses of α-Nrxn KO mice (45). Even more importantly, α-Nrxn is abundantly expressed in glutamatergic neurons as well (12) and has unequivocal effects on release from excitatory synapses (9,44,46,78).…”
Section: Discussionmentioning
confidence: 87%
“…In addition, research has identified several molecules, mostly ion channels and receptors, which are functionally impaired when Nrxn expression is altered. Nrxn variants have been found to affect voltage-dependent calcium channels (9,10), GABA A R (7, 37), NMDAR (44), GABA B R (36,45), nicotinergic acetylcholine receptors (69), and AMPAR (47). These ionotropic and metabotropic receptors represent "target molecules" of Nrxn that may include some physical association, but it appears unlikely that the functional link to all these requires stable protein-protein interactions.…”
Section: Discussionmentioning
confidence: 99%
“…Neurexin 1/2/3-triple knock-out animals die perinatally and have reduced spontaneous and evoked neurotransmission at glutamatergic and GABAergic synapses, demonstrating that -neurexins are necessary for neurotransmitter release at synapses (Missler et al, 2003). Additionally, mice lacking neurexins have impaired neuroendocrine secretion (Dudanova et al, 2006), which may mirror some children with autism that exhibit dysfunction of the hypothalamic-pituitary-adrenocortical system, possibly due to altered neuroendocrine regulation (Corbett et al, 2006). Similar to the neurexin triple knockout animals, mice lacking neurexin1/2 or neurexin2/3 die within 1 month after birth and have reduced neurotransmission.…”
Section: Neurexin and Neuroligin Deficits In Asdmentioning
confidence: 99%
“…Therefore, understanding their targeting to presynaptic and postsynaptic compartments appears mandatory. Nrxns exist and function predominantly at the presynaptic terminal (Ushkaryov et al, 1992;Dean et al, 2003;Missler et al, 2003;Graf et al, 2004;Dudanova et al, 2006;Berninghausen et al, 2007;Li et al, 2007;Taniguchi et al, 2007), although a small but relevant population at the postsynapse is possible (Kattenstroth et al, 2004;Taniguchi et al, 2007). Neuroligins are present almost exclusively at the postsynaptic compartment (Ichtchenko et al, 1995;Song et al, 1999;Scheiffele et al, 2000;Varoqueaux et al, 2006;Berninghausen et al, 2007).…”
Section: Introductionmentioning
confidence: 99%